2017
DOI: 10.1016/j.athoracsur.2017.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Technical Performance Score: Predictor of Outcomes in Complete Atrioventricular Septal Defect Repair

Abstract: At our center, CAVSD repair was associated with low morbidity. TPS may identify patients with complications, prolonged days on ventilator, and who require postdischarge reinterventions; thus, it provides feedback on areas of improvement and allows identification of patients who warrant closer follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Earlier studies suggested the TPS was useful in predicting both short and midterm clinical outcomes, neurodevelopmental outcomes, and costs. [3][4][5][6][7][8][9][10][11][12][13][14][15] However, most studies on TPS were based on a single-center experience. The score name was changed from TPS to RLS in the planning phase of the RLS study because the term TPS may be construed to imply that residual lesions are exclusively the result of the surgeon's technical performance, whereas they may also be a function of the underlying anatomy, the completeness and accuracy of preoperative assessment, and/or intraoperative decision making in which a residual lesion is recognized but deemed to be inconsequential or even therapeutic.…”
Section: Perspectivementioning
confidence: 99%
“…Earlier studies suggested the TPS was useful in predicting both short and midterm clinical outcomes, neurodevelopmental outcomes, and costs. [3][4][5][6][7][8][9][10][11][12][13][14][15] However, most studies on TPS were based on a single-center experience. The score name was changed from TPS to RLS in the planning phase of the RLS study because the term TPS may be construed to imply that residual lesions are exclusively the result of the surgeon's technical performance, whereas they may also be a function of the underlying anatomy, the completeness and accuracy of preoperative assessment, and/or intraoperative decision making in which a residual lesion is recognized but deemed to be inconsequential or even therapeutic.…”
Section: Perspectivementioning
confidence: 99%
“…Given the complexity of the repair and the anatomy of the AVVs, a second bypass run is not uncommon in CAVSD repair [20,21], yet rarely reported. In this study, the use of a second bypass run to correct residual lesions was effective, with 74% of these patients having the residual defect corrected.…”
Section: Commentmentioning
confidence: 99%
“…2 A previous study has shown that the presence of residual lesions before discharge, as measured by TPS, accurately identifies patients requiring postdischarge reinterventions (PD-RI). 3 However, in this previous study, overall TPS was used to determine the association between TPS and PD-RI. The association between individual subcomponents of TPS and PD-RI was not investigated.…”
mentioning
confidence: 99%
“…Patients with associated major intracardiac anomalies or partial/transitional AVSD were excluded. Postoperative TPS was determined as previously reported 3 based on predischarge echocardiographic findings and clinical status at discharge from the index operation. The TPS for CAVSD repair included the following subcomponents: size of residual atrial septal defect, size of residual ventricular septal defect (VSD), severity of right and left atrioventricular valve (AVV) stenosis and regurgitations, status of the patent ductus arteriosus, and status of the conduction system.…”
mentioning
confidence: 99%
See 1 more Smart Citation